Three novelties in Ecuadorian Blakea (Pyxidantheae, Melastomataceae) with information on their pollination biology - Urrea, Johan; Penneys, Darin S.; Fernández-Fernández, Diana; Dellinger, Agnes S.; Lazarus, Benjamin S.; Ulloa, Carmen Ulloa; Durbin, Kira H.; Hetz, Jacob P. (Phytotaxa, 2026)
Field work in the Western Cordillera of Ecuador has led to the discovery of several undescribed Melastomataceae, among them three species of Blakea treated here. Blakea antennata is the fourth vertebrate-pollinated species of the genus discovered in the Andes, and its most unusual morphological feature is the minute, antenna-shaped, anther connective appendage. Blakea gorgona is readily distinguished by its large subsessile leaves, multiflorous fascicles, elongate scales on the nodes, bract apices, and calyx lobes, hair tufts along inner rim of torus, and mildew-scented flowers. Blakea rubiginosa has, compared to its closest presumed relatives, longer petioles, larger leaves and inner floral bracts, and irregularly rupturing calyx lobes. Each species is described, illustrated, mapped, compared with presumed relatives, and its pollination biology is discussed. A preliminary conservation status of Endangered (EN) is recommended for all three species based on IUCN Red List Categories and Criteria.